Legal Culture as Public Phenomenon and Problems of Forming it in School-Children - T V Vorontsova; A V Savelyeva (Peoples' Friendship University of Russia (RUDN University), 2013)
In the article the place and role of legal culture in the context of general culture of the personality and society are considered; the basic theories of the formation of legal culture are submitted; the problems and pedagogical conditions of legal culture education of school-children are covered.